2021
DOI: 10.1016/j.worlddev.2020.105260
|View full text |Cite
|
Sign up to set email alerts
|

The impact of iron-biofortified bean adoption on bean productivity, consumption, purchases and sales

Abstract: Highlights We estimate the impact of adoption of RWR2245, a popular iron-biofortified bean released in Rwanda. Adoption provides a yield gain of 20%-49% over that of local bush bean varieties. Adoption increases household consumption of beans from own production and reduces bean purchases. Adoption increases the probability that households sell beans by 12%. RWR2245 increases iron intake among adopting households and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Further analysis of this data showed that adoption of the most popular iron bush bean variety in Rwanda resulted in a yield gain of 20-49 percent over traditional bush bean varieties. This effectively increased the length of time beans are consumed from own production (as opposed to through purchased beans) by almost three weeks, while increasing the probability of selling beans by 12% ( Birol Vaiknoras and Larochelle, 2021 ). These results indicate that iron bean production has positively and significantly improved both food and nutrition security, as well as livelihood security, among adopting households.…”
Section: Socio-economic Research Methods and Resultsmentioning
confidence: 99%
“…Further analysis of this data showed that adoption of the most popular iron bush bean variety in Rwanda resulted in a yield gain of 20-49 percent over traditional bush bean varieties. This effectively increased the length of time beans are consumed from own production (as opposed to through purchased beans) by almost three weeks, while increasing the probability of selling beans by 12% ( Birol Vaiknoras and Larochelle, 2021 ). These results indicate that iron bean production has positively and significantly improved both food and nutrition security, as well as livelihood security, among adopting households.…”
Section: Socio-economic Research Methods and Resultsmentioning
confidence: 99%
“…A secondary analysis investigated the effect of the most widely adopted high-iron bean cultivar, RWR2245, on bean consumption among 1400 households [ 32 , 33 ]. Over a 12-month period, growing RWR2245 for at least one of the two growing seasons increased the length of time beans were consumed from farmers’ own production by ~20 days.…”
Section: Resultsmentioning
confidence: 99%
“…Such breeding interventions have also been applied to develop high-yield legumes with a high micronutrient content, such as Fe biofortified beans. They are designed to address Fe deficiency, one of the most common micronutrient deficiencies globally ( 114 ) which causes anemia, fatigue, increased risk of infection, and pregnancy complications ( 130 ). Unfortunately, plant-based diets found in developing countries have low Fe bioavailability containing almost exclusively non-haeme iron, often absorbed less than 10% respect to haeme iron ( 113 , 132 ).…”
Section: Common Beans As a Key Legumementioning
confidence: 99%